การพัฒนากลยุทธ์การบริหารห้องสมุดโรงเรียนเพื่อเสริมสร้างทักษะการเรียนรู้ด้วยการนำตนเอง ของนักเรียนประถมศึกษา - เลิศวีระศิริกุล, บุษกร (บรรณศาสตร์ มศว, 2014)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ 1) ศึกษาสภาพปัจจุบันและสภาพที่พึงประสงค์ของการบริหารห้องสมุดโรงเรียนเพื่อ เสริมสร้างทักษะการเรียนรู้ด้วยการนำตนเองของนักเรียนประถมศึกษา 2) วิเคราะห์จุดแข็ง จุดอ่อน โอกาส และภาวะคุกคาม ของการบริหารห้องสมุดโรงเรียนเพื่อเสริมสร้างทักษะการเรียนรู้ด้วยตนเองของนักเรียนประถมศึกษา และ 3) พัฒนากลยุทธ์ การบริหารห้องสมุดโรงเรียนเพื่อเสริมสร้างทักษะการเรียนรู้ด้วยการนำตนเองของนักเรียนประถมศึกษา ใช้วิธีวิจัยแบบผสม ผสาน ได้แก่ วิธีวิจัยเชิงปริมาณ ซึ่งใช้แบบสอบถามในการเก็บข้อมูลจากกลุ่มตัวอย่างที่เป็นโรงเรียนประถมศึกษา จำนวน 395 โรงเรียน และวิเคราะห์ข้อมูลด้วยสถิติบรรยาย และวิเคราะห์ลำดับความต้องการจำเป็นด้วยเทคนิคการประเมินความ ต้องการจำเป็น (PNImodified) ส่วนวิธีวิจัยเชิงคุณภาพ เก็บรวมรวมข้อมูลด้วยแบบสัมภาษณ์ซึ่งกำหนดกลยุทธ์จากตาราง TOWS Matrix จากกลุ่มตัวอย่างที่เป็นผู้บริหารห้องสมุดโรงเรียนประถมศึกษาที่ได้รับรางวัลห้องสมุดดีเด่นระดับประถม ศึกษา จำนวน 3 แห่ง และได้รับการประเมินและตรวจสอบกลยุทธ์โดยผู้เชี่ยวชาญ ผลการวิจัยพบว่า การบริหารห้องสมุดโรงเรียนเพื่อเสริมสร้างทักษะการเรียนรู้ด้วยการนำตนเองของนักเรียนประถม ศึกษา มีสภาพปัจจุบันโดยรวมอยู่ในระดับน้อยที่สุด ทั้งการวางแผน การนำแผนสู่การปฏิบัติและการประเมินผล มีสภาพที่ พึงประสงค์โดยรวมอยู่ในระดับมาก ทั้งการวางแผน การนำแผนสู่การปฏิบัติและการประเมินผล นอกจากนี้ยังพบว่า กลยุทธ์ การบริหารห้องสมุดโรงเรียนเพื่อเสริมสร้างทักษะการเรียนรู้ด้วยการนำตนเองของนักเรียนประถมศึกษา ประกอบด้วย 3 กลยุทธ์ หลัก คือ 1) กลยุทธ์พลิกระบบการประเมินผลเพื่อเสริมสร้างทักษะการเรียนรู้ด้วยการนำตนเองของนักเรียนประถมศึกษา 2) กลยุทธ์ปลุกวิถีการนำแผนสู่การปฏิบัติเพื่อเสริมสร้างทักษะการเรียนรู้ด้วยการนำตนเองของนักเรียนประถมศึกษา และ 3) กลยุทธ์จุดประกายการวางแผนเพื่อเสริมสร้างทักษะการเรียนรู้ด้วยการนำตนเองของนักเรียนประถมศึกษา Abstract The objectives of this research aimed to 1) explore the current and ideal/ expected library management system to support self-directed learning of primary school students 2) to understand strange, weakness, opportunity and threat of library management system for self-directed learning of primary school students and 3) develop strategies for library management system to support self-directed learning of elementary school students. This research applied a mixed method approach. The quantitative information was gathered from 395 elementary schools. The qualitative information and data was taken from interview about the best practice school library and the best librarian from 3 elementary school libraries. The research instruments included interview form. The strategies were generated from TOWS Matrix. The instruments included questionnaires and interview forms. Data were analyzed using descriptive statistics and the technique called Priority Needs Index (PNImodified) was applied. The proposed strategies were verified by the experts. The results showed that: The current situation of library management system to support self-directed learning of elementary school students was rated at the lowest level both planning, implementation and evaluation. The expected situation of library management system to support self-directed learning of elementary school students was rated at a high level both planning, implementation and evaluation. Regarding the development of school library management strategies to support self–directed learning of elementary school students, there are three: 1) The strategy for turning over evaluation system to Support Self–Directed Learning of Elementary School Students 2) The strategy for put the plan into action to Support Self–Directed Learning of Elementary School Students 3) The strategy for inspire the planning to support self–-directed learning of elementary school students คำสำคัญ: การบริหารห้องสมุดโรงเรียน การเรียนรู้ด้วยการนำตนเอง นักเรียนประถมศึกษา Keyword: Library management system, Self-directed learning, Elementary school students